An integrated methodology to manage risk factors of aging urban oil and gas pipelines. (July 2020) - Li, Xinhong; Han, Ziyue; Zhang, Renren; Abbassi, Rouzbeh; Chang, Dawei
Abstract: Aging urban oil and gas pipelines have a high failure probability due to their structural degradation and external interference. The operational safety of the aging urban oil and gas pipeline is challenged by different hazards. This paper proposes a novel methodology by integrating an index-based risk evaluation system and fuzzy TOPSIS model for risk management of aging urban oil and gas pipelines, and it is carried out by evaluating the priority of hazards affecting pipeline safety. Firstly, the hazard factors of aging urban oil and gas pipelines are identified to establish an index-based risk evaluation system. Subsequently, the fuzzy TOPSIS model is employed to evaluate the importance of these hazard factors and to decide which factors should be managed with priority. This work measures the importance of a hazard factor from three aspects, i.e. occurrence (O), severity (S) and detectability (D), and the weights of these three parameters are determined by a combination weight method. Eventually, the proposed methodology is tested by an industrial case to illustrate its effectiveness, and some safety strategies to reduce the operational risk of the pipeline are presented. The proposed methodology is a useful tool to implement more efficient risk management of aging urban oil and gas pipelines. Highlights: ● A novel methodology for risk management of aging urban oil and gas pipelines is proposed. ● An index-based risk evaluation model for aging urban oil and gas pipelines is established. ● Importance of hazards is evaluated by a fuzzy TOPSIS model. ● Some pertinent measures are proposed to control the operational risk of aging urban pipelines.